2013
DOI: 10.3109/02699052.2013.775492
|View full text |Cite
|
Sign up to set email alerts
|

Speech pathologists’ current practice with cognitive-communication assessment during post-traumatic amnesia: A survey

Abstract: The study confirmed that speech pathologists have a key role in the multidisciplinary team caring for the person in PTA, especially with family education and facilitating interactions with the rehabilitation team and family. Decision-making around timing and means of assessment of cognitive-communication during PTA appeared primarily reliant on speech pathologists' professional experience and the culture of their workplace. The findings support the need for further research into the nature of cognitive-communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 46 publications
5
20
0
1
Order By: Relevance
“…The study provided the views of only a small number (n=19) of SLPs. However this number is representative of SLPs currently working in this specialised population within Australia 41 , is similar to numbers reported in other studies for this SLP population 45,46 , and respondents were, for the most part, experienced clinicians. This study investigated services only within one country, however these rehabilitation services are provided under guidelines that utilise the ICF framework.…”
Section: Limitationssupporting
confidence: 86%
“…The study provided the views of only a small number (n=19) of SLPs. However this number is representative of SLPs currently working in this specialised population within Australia 41 , is similar to numbers reported in other studies for this SLP population 45,46 , and respondents were, for the most part, experienced clinicians. This study investigated services only within one country, however these rehabilitation services are provided under guidelines that utilise the ICF framework.…”
Section: Limitationssupporting
confidence: 86%
“…There was a significant difference between geographical location and years of experience. SLPs with greater than 10 years of experience were less likely to work in rural and remote areas than SLPs with less than 10 years' experience, 2 …”
Section: Demographic Informationmentioning
confidence: 96%
“…SLP assessment and intervention commences in the acute setting with a focus primarily on dysphagia management [1], observation and monitoring of communication abilities during post-traumatic amnesia [2] and further on in the rehabilitation process SLPs have an important contribution in cognitive rehabilitation, with assessment and management of cognitive communication disorders [3]. Rehabilitation after a TBI is a specialized field and requires expert clinical decision-making skills where there is an understanding of the person's impairments in communication and how this relates to their ability to participate in real life activities [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of speech-language pathologists looking at the practice of evaluation of cognitive-communication skills showed that most clinicians initiated formal testing only on emergence from PTA [63]. There has not been any formal research regarding the optimum timing of standardized assessment in speech-language pathology, but some evidence is available in related fields [63].…”
Section: Discussionmentioning
confidence: 99%